Relación de la conciencia emocional de los padres de familia con el desarrollo moral de los estudiantes del 2do grado de secundaria de la I.E Clemente López Montalván - Belda Neciosup, Sofía Irene (2011)
Show it(subj) basic investigation was orientated to the educational institutionls relation of the emotional conscience of the family men with the moral development of the students of the second secondary- education grade the secondary leve\ls Cle lópez Montalván 1 once San Martín1S department was located in the road surface, province district of Moyobamba. present study has for objective To determine the relation among the family men's emotional conscience of family and the moral development of the students of the second secondary- education grade of the lnstitution Educativa Cle lópez Montalván of Calzada's district. Starting from a former study after transversa facto - correlaciona! , and determining the relation grade among the variables , they utilized the theoretic methods of induction , analysis 1 synthesis , as well as the empiric measurement methods and statistical methods , 1 have a meal also , and he polls individual to establish the perception level to the parents and students. In the intention of checking them hypothesis 1 it has happened to me that they have recollected information of the lnstitution Educativa Cle lópez Montalván , of 45 family men , applying a 17- items test and to 45 students of the secondary levei1S Second grade , correspondent to the VIl Ciclo of Regular Basic education , with a 12- items opinion poll's application. With the statistical test , he became established than exist relation among the Conciencia Emocional of the parents of family and the children's Desarrollo Moral students of the ( 2do 1 harrow ) of Educación Secondary, Obteniéndose a value once was calculated ofYc =0,572~ principal than the tabular value of Ya =0,288, morar development brings near product of the hushed knowledge that the family men have.